2014
DOI: 10.1523/jneurosci.4488-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type-Specific Expression Analysis to Identify Putative Cellular Mechanisms for Neurogenetic Disorders

Abstract: Recent advances have substantially increased the number of genes that are statistically associated with complex genetic disorders of the CNS such as autism and schizophrenia. It is now clear that there will likely be hundreds of distinct loci contributing to these disorders, underscoring a remarkable genetic heterogeneity. It is unclear whether this genetic heterogeneity indicates an equal heterogeneity of cellular mechanisms for these diseases. The commonality of symptoms across patients suggests there could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
280
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(291 citation statements)
references
References 67 publications
11
280
0
Order By: Relevance
“…P < 0.05) using cell type-specific expression analysis (34). Whereas DEGs common to both the 10 mg/kg and 30 mg/kg groups were enriched in genes expressed in striatal medium spiny and cortical project neurons ( Figure 7A), DEGs specific to the 30 mg/kg group were additionally enriched in transcripts expressed in cholinergic neurons ( Figure 7B).…”
Section: Resultsmentioning
confidence: 99%
“…P < 0.05) using cell type-specific expression analysis (34). Whereas DEGs common to both the 10 mg/kg and 30 mg/kg groups were enriched in genes expressed in striatal medium spiny and cortical project neurons ( Figure 7A), DEGs specific to the 30 mg/kg group were additionally enriched in transcripts expressed in cholinergic neurons ( Figure 7B).…”
Section: Resultsmentioning
confidence: 99%
“…6B). Finally, we used a recently developed tool-cellspecific expression analysis (Xu et al 2014)-to examine within which brain regions and cellular populations the conserved FoxP1 targets are enriched. We found that DEGs down-regulated with loss of Foxp1 and up-regulated with overexpression of FOXP1 are enriched for striatal genes (Fig.…”
Section: Conserved Regulation Of Foxp1 Targets Within the Striatummentioning
confidence: 99%
“…While there is a strong genetic component to ASD, this is divided among several hundred genes, each with only a small contribution to the prevalence of the disorder (Geschwind and State 2015). Furthermore, many autismrisk genes are thought to exert their effects during early brain development (State and Sestan 2012;Xu et al 2014;Parikshak et al 2015). Transcription factors play a key role in orchestrating the spatial and temporal gene expression patterns important for this process.…”
mentioning
confidence: 99%
“…Regional markers were originally determined using existing gene expression data from the Atlas of the Developing Human Brain (www.brainspan.org); cell-type markers were originally derived via translational profiling of genetically tagged cell lines isolated from mouse brain. 36 Marker enrichment was tested through the Fisher's Exact test.…”
Section: Snp-enrichment Analysismentioning
confidence: 99%
“…In order to determine whether the modules detected in our data set are part of regionally restricted network, we tested their enrichment in gene expression markers of distinct brain regions and cell types. 36 Figure 3 presents the results from this analysis at pSI 0.001 (see Materials and Methods). Of the two modules (M5 and M7) that previously showed a trend for association with BD based on eigengene expression, M7 was found to be enriched in markers for immune cells, whereas M5 showed no cell-type or regional marker enrichment.…”
Section: Enrichment Of De Genes In Canonical Pathwaysmentioning
confidence: 99%